2017
DOI: 10.1021/acs.chemmater.6b05369
|View full text |Cite
|
Sign up to set email alerts
|

Dual Substitution Strategy to Enhance Li+ Ionic Conductivity in Li7La3Zr2O12 Solid Electrolyte

Abstract: Solid state electrolytes could address the current safety concerns of lithium-ion batteries as well as provide higher electrochemical stability and energy density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
132
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(147 citation statements)
references
References 47 publications
13
132
1
1
Order By: Relevance
“…Among the garnet-type oxide compounds, Li 7−x La 3 Zr 2−x Nb x O 12 (LLZNb) 8,9 and Li 7−x La 3 Zr 2−x Ta x O 12 (LLZTa) 1012 , in which a part of the zirconium site in Li 7 La 3 Zr 2 O 12 (LLZ) 1315 is substituted with niobium and/or tantalum, are very attractive because they have the highest lithium-ion conductivity and a wide potential window. Recently, there are many reports that LLZ of the garnet-type solid electrolyte partially replaced with Ga and/or Sc and Al has high ionic conductivity of 10 −3 order 1719 . Furthermore, it has been reported that the space group changes from the ordinary Ia -3 d to I -43 d in the system in which Ga is substituted from the result of detailed single crystal structure analysis 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the garnet-type oxide compounds, Li 7−x La 3 Zr 2−x Nb x O 12 (LLZNb) 8,9 and Li 7−x La 3 Zr 2−x Ta x O 12 (LLZTa) 1012 , in which a part of the zirconium site in Li 7 La 3 Zr 2 O 12 (LLZ) 1315 is substituted with niobium and/or tantalum, are very attractive because they have the highest lithium-ion conductivity and a wide potential window. Recently, there are many reports that LLZ of the garnet-type solid electrolyte partially replaced with Ga and/or Sc and Al has high ionic conductivity of 10 −3 order 1719 . Furthermore, it has been reported that the space group changes from the ordinary Ia -3 d to I -43 d in the system in which Ga is substituted from the result of detailed single crystal structure analysis 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Oxide solid electrolytes are further classified into glass, glass‐ceramic, and crystalline types. Crystalline solid electrolytes include LISICON, perovskite, β‐alumina with Na + /Li + ion exchange, and garnet types . Li 7– x La 3 Zr 2– x Nb x O 12 , and Li 7– x La 3 Zr 2– x Ta x O 12 ,,,, in which part of Li 7 La 3 Zr 2 O 12 ,, is substituted with niobium or tantalum, has high lithium ion conductivity and a wide potential window.…”
Section: Introductionmentioning
confidence: 99%
“…Li 7– x La 3 Zr 2– x Nb x O 12 , and Li 7– x La 3 Zr 2– x Ta x O 12 ,,,, in which part of Li 7 La 3 Zr 2 O 12 ,, is substituted with niobium or tantalum, has high lithium ion conductivity and a wide potential window. Recently, many reports have shown that the Li 7 La 3 Zr 2 O 12 of garnet solid electrolytes partially replaced with Ga and/or Sc and Al has high ionic conductivity on the order of 10 −3 ,,. Previously, we reported for the first time that single crystals of garnet type solid electrolyte can be grown by the floating zone (FZ) method which is one of melting methods .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, components with high denseness have been fabricated by electric current sintering and hot press methods, and there are reports of lithium ion conductivity of 10 -3 S/cm order. [20]- [22] Although the denseness of components is increasing, there are also new reports of internal shortcircuiting. [3][6] [12][13] [15] The problem of internal short-circuits is that short-circuits occur between positive and negative electrodes due to precipitation of lithium metal within an allsolid-state lithium secondary battery.…”
Section: Garnet-type Lithium Solid Electrolytementioning
confidence: 99%